Analysis of the need for gamification in writing fantasy texts at state Islamic Junior High Schools - Maudina Lutfiyani; Yeti Mulyati; Rudi Adi Nugroho; Khaerudin Kurniawan; Halimah Halimah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This study was motivated by the low motivation and ability of junior high school students to write fantasy texts, which require a high degree of imagination and narrative skills. Students struggle to express their ideas, develop a plot, and write coherently, while teachers' teaching methods tend to be conventional and lack interactivity. This study aims to analyze the need for gamification in fantasy writing instruction to enhance students' motivation, creativity, and writing skills. The study employs a qualitative descriptive method with a needs analysis approach. Data were collected through classroom observations, semi-structured interviews, and questionnaires involving 29 students and two Indonesian language teachers. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that most students experienced difficulties in developing ideas and had relatively low writing motivation, despite demonstrating a high level of imaginative interest in the world and characters of fantasy. These findings underscore the need for instructional materials that provide structured support and offer engaging learning experiences as a foundation for designing gamification-based fantasy text instructional materials in subsequent development stages.